PERAN HUMAN CAPITAL DALAM MENINGKATKAN DAYA SAING ORGANISASI DI ERA TRANSFORMASI DIGITAL - Dewi Alfiah Febriani; Jinani Firdausi; Dela Nafisyah Ali; Dita Utari Yulia Putri; Zainuna Ivada; Karin Syafira Widiyanto; Siti Sulasmi Kholifah; Nur Mauliddyah Rosanti; Novia Dwi Afrilianti (CV. Denasya Smart Publisher, 2025)
Digital transformation has brought significant changes to the way organizations operate and compete in the global market. Amidst this shift, human capital has become a vital element in determining organizational success, not merely as a supporter of technology, but as the primary driver of innovation, efficiency, and competitiveness. This study aims to investigate the strategic role of human capital in enhancing organizational competitiveness in the digital age. Using a descriptive qualitative approach based on literature review, the study reveals that the development of digital competencies, a responsive organizational culture, and technology-based human resource management systems significantly influence the enhancement of competitive advantage. Additionally, the integration of technology and the reinforcement of human values are considered essential for achieving organizational sustainability. This study contributes conceptually to strengthening the Human Capital Management (HCM) paradigm and serves as a foundation for developing more adaptive human resource strategies in response to the demands of the digital age